Spatial Movement Analysis With Space Syntax After Covid-19 Pandemic: A Case Study In Micro And Macro Scale - Musyaffa Rifqi Hari Mardika; Handri, Hannisa; Pratiwi, Intan Agustina; Ilmi, Muhammad Rasyidul; Nurfadillah, Achnia Tiffany (Journal of Synergy Landscape, 2025)
The COVID-19 pandemic has significantly altered spatial behavior and public space configurations. This study employs Space Syntax methodology to analyze spatial movement patterns in both micro (interior) and macro (urban) scales, highlighting how spatial configurations can support social distancing and minimize contagion risk. By examining spatial typologies (Spaces a–d), the research identifies how integration and segregation values influence circulation and encounter potential. A comparative analysis between pre- and post-COVID layouts—such as in museum settings and urban districts in Qatar—reveals how certain spatial systems (notably Space d) enhance spatial legibility and traceability, while others (Space c) promote flexible circulation cycles. Results suggest that strategic configuration of spatial elements can act as passive disease-mitigation tools, emphasizing the role of architects in designing resilient spaces. This study contributes to the discourse on post-pandemic design by proposing a “scale of contagion” framework for evaluating spatial vulnerability and adaptability, and further argues that architectural practice must evolve by embedding epidemiological insight into the core of spatial planning—ensuring that future environments are both socially responsive and resilient to public health challenges.